VO.14 Adjust unit price for R.C.C works in foundation with water proofing admixture - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the VO.14 adjust unit price for R.C.C works in foundation with water proofing admixture of BRACU new campus project site.